Plant Contact Dermatitis in 2021 - Rozas-Muñoz, Eduardo; Gamé, Denise; Mir-Bonafé, Juan-Francisco; Piquero-Casals, Jaime (Current treatment options in allergy, 2022)
Purpose of the Review Allergic contact dermatitis to plants is a complex and common condition of the dermatologic practice. The large number of plants and associated allergens has hampered a better understanding of this topic by the common medical practitioners and dermatologist. Recent Findings The number of new species and associated allergens, involved in allergic contact dermatitis of plants, has increased in the last years. Different approaches to the subject have been proposed, but the chemical classification seems useful, as it may predict cross-reactivity between different plant species. Summary We review the most common species of plants involved in allergic contact dermatitis by grouping them according to their main associated allergens. This classification includes five groups: α-methylene-γ-butyrolactones, phenol derivatives, quinones, terpenes and miscellaneous structures (disulfides, isothiocyanates or polyacetylenic derivates). The most important clinical manifestations and the recommended patch testing are also described.